Green synthesis of metal nanoparticles, characterization, and biosensing applications - Chiravoot Pechyen; Benchamaporn Tangnorawich; Surachet Toommee; Robert Marks; Yardnapar Parcharoen (Sensors International)
This comprehensive review provides an in-depth overview of the green (biological) synthesis, characterization, and biosensor applications of metal nanoparticles (NPs). Because of their unique physical and chemical properties, high surface area, and nanoscale size, NPs have become crucial in various fields. The review emphasizes the synthesis, properties, and applications of several metal NPs, particularly silver (AgNPs), gold (AuNPs), platinum (PtNPs), copper (CuNPs), zinc oxide (ZnONPs), iron oxide (FeONPs), and palladium (PdNPs). Green synthesis methods, a truly innovative approach, utilize biological substances such as plant extracts, bacteria, fungi, and yeast. These methods offer environmentally friendly and biologically compatible alternatives to conventional chemical synthesis techniques. This review details these sustainable approaches and their advantages over traditional methods. These natural sources provide an abundant, cost-effective, and environmentally sustainable alternative for NP production. The importance of thorough characterization of nanoparticles is also discussed, highlighting techniques such as transmission electron microscopy (TEM), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and UV–Vis spectroscopy to analyze the size, shape, surface properties, structural integrity, and optical behavior of the NPs. The review highlights the vast potential of metal NPs in biosensors, which play a critical role in medical diagnostics, environmental monitoring, and food safety. Incorporating metal NPs in electrochemical, optical, thermometric, and piezoelectric biosensors significantly enhances sensitivity and specificity, enabling rapid and real-time detection of various analytes.